Pet ownership and mental health : pet ownership, well-being, mental health and the effect on depression and anxiety - Björk Ólafsdóttir 1976- (2017)
The rate of mental health disorders has been increasing over the last years and is becoming a large societal problem worldwide. Individuals suffering from mental health disorders are believed to be less happy and evaluate their mental health to be lower than those who are not suffering. Today, depression and anxiety are the two most common mental health disorders and threaten many people’s lives. Companion animals have been proposed as a prevention and a treatment measure. The aim of the study was to investigate whether pet owners were different from non-pet owners in this regard, i.e. whether they evaluated their mental health to be better than non-owners or were less likely to suffer from symptoms of depression and anxiety disorders. Also to investigate whether pet-owners who spent much time with their pets were less likely to suffer from symptoms of depression and anxiety disorders than pet owners who spent little time with their pets. Participants (N = 1.228) from a Gallup study, the researcher’s Facebook friend list and undergraduate psychology and business students at the University of Reykjavík, participated in this study and their age was 18 years and older. The DASS-21 scale was used to measure depression, anxiety and stress symptoms. The results showed that there was no significant mean difference on depression and anxiety symptoms between pet- and non-pet owners. Also, there was no significant mean difference on depression and anxiety symptoms between pet owners who spent much time with their pets than those who spent little time with their pets. The results also showed that males who allowed their pets to sleep in their beds showed more symptoms of anxiety compared to females who allowed their pets to sleep in their beds. Keywords: pet ownership, well-being, mental health, depression, anxiety Á ári hverju aukast geðræn vandamál í heiminum sem stuðla að ýmsum samfélagslegum vandamálum. Einstaklingar sem þjást af geðrænum vanda eru líklegri til að meta andlega líðan sína sem verri en þeir sem ekki ...